Environmental Indicators – Agri-Environmental Indicators - Katonáné Kovács, Judit (Acta Agraria Debreceniensis, 2004)
close relation. This means that policies related to the economy and the environment cannot be handled without each other. The United Nations Conference (Stockholm, 1972) was the first global conference to signal that environment concerns have increasingly become subject of mainstream socio-economic policies. The process started in the Seventies, laying emphasis on environment protection, plays an important role in the policy of international agencies. The use of environmental indicators is essential for monitoring the effects of environmental measures. The best way of evaluating sustainability if the results can be compared on a global level. International efforts are being made by the United Nations (UN), the Organisation for Economic Co-operation and Development (OECD), the Statistical Office of the European Commission (Eurostat) and other international agencies to develop a framework for environment statistics. This study deals with these frameworks, paying attention to agri-environment indicators. Hungary became a member of the UN in 1955, of the OECD in 1996, and will become a member of the European Union in 2004. The first summary in connection with environmental indicators of Hungary, taking the OECD Pressure – State – Response framework as a basis, was published in 1994. As a result, comparability of environmental indicators for Hungary with those used international are given.